2018
DOI: 10.1111/1541-4329.12136
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Analysis of Food Safety Competences at Elementary and Upper‐Secondary Level of Formal Education Inside Food‐Related Programs in Slovenia

Abstract: Since formal education is guided through food-related curricula, there is a concern regarding to which extent food safety elements are supported in the current educational objectives presented in syllabi. The aim of this study was to analyze the existing food safety elements in the syllabi at the elementary (for students between 6 and 14 y of age) and upper-secondary level (food-related programs) of formal education (for students between 15 and 18 y of age). Analysis was done through predefined criteria, evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“… 20 One of the important factors needed to teach food safety in teachers in Slovenia, besides the curriculum, was sufficient knowledge and a positive attitude towards food safety. 8 Primary and secondary school educators in Romania reported that food hygiene and related risks was one of the most important topics that they, as educators, wished to learn in the context of nutrition and health and food safety. 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 One of the important factors needed to teach food safety in teachers in Slovenia, besides the curriculum, was sufficient knowledge and a positive attitude towards food safety. 8 Primary and secondary school educators in Romania reported that food hygiene and related risks was one of the most important topics that they, as educators, wished to learn in the context of nutrition and health and food safety. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored children and young peoples' knowledge and behaviours towards food hygiene and safety in the UK, Europe and USA, [4][5][6][7][8][9] but studies exploring educator views are limited. In a small study, UK teachers reported that the most effective method to teach food hygiene and to reinforce food safety messages was with demonstrations of good practice and practical activities involving young people preparing food.…”
mentioning
confidence: 99%
“…For the identification of food safety knowledge gaps among students of different background, two groups of faculties were identified, namely food/health related faculties such as Food Technology, Veterinary Medicine and Medicine and non-food/health related faculties included Faculty of Agriculture, Economics and Faculty of Philology. Non-food/ health related faculties do not offer courses where food safety issues are discussed, and it is assumed that students' knowledge mainly originate from the previous formal (elementary and secondary schools) and informal education (Ovca et al, 2018), as well as from private home, family and friends, media, Internet, etc. (Byrd-Bredbenner et al, 2007;Lazou et al, 2012).…”
Section: Knowledge Gapsmentioning
confidence: 99%
“…Moreover, these FS topics are restricted to and taken by HE majors only. With this problematic treatment and placement of FS topics in the curriculum, it becomes imperative to develop a separate CG that is primarily designed for the delivery of FS education in classrooms, particularly in High School (Diplock et al 2017(Diplock et al , 2019Ovca et al 2018;Shearer et al 2013;.…”
Section: Discussionmentioning
confidence: 99%